2000
DOI: 10.1007/s004420050980
|View full text |Cite
|
Sign up to set email alerts
|

Marine nutrient contributions to freshwater apex predators

Abstract: Recent investigations into the nutrient cycling of coastal ecosystems have suggested that migratory or anadromous fish could be important vectors of marine nutrients. Anadromous fish have assimilated marine nutrients that would contribute to the nutrient budgets of freshwater systems by excretion, gamete release, or the decay of post-reproductive carcasses. However, the extent to which freshwater predators utilize marine material is not well understood. In systems where anadromous fish temporarily constitute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 27 publications
2
74
1
Order By: Relevance
“…Therefore, any catfish heavily relying on this prey source ought to show corresponding decrease in δ 15 N values, which was not evident. Catfish are known to feed on many anadromous species, which would reflect marine δ 13 C values when migrating from marine to freshwater habitats, and feeding on prey with such distinct δ 13 C values can quickly elevate the δ 13 C values of catfish (MacAvoy et al 2000). But migrations of anadromous fish are effectively prevented by damming in the Tarn River, so any dietary contribution from anadromous fish with elevated δ 13 C values is unlikely.…”
mentioning
confidence: 99%
“…Therefore, any catfish heavily relying on this prey source ought to show corresponding decrease in δ 15 N values, which was not evident. Catfish are known to feed on many anadromous species, which would reflect marine δ 13 C values when migrating from marine to freshwater habitats, and feeding on prey with such distinct δ 13 C values can quickly elevate the δ 13 C values of catfish (MacAvoy et al 2000). But migrations of anadromous fish are effectively prevented by damming in the Tarn River, so any dietary contribution from anadromous fish with elevated δ 13 C values is unlikely.…”
mentioning
confidence: 99%
“…The body 65 Cu/ 63 Cu ratio varies according to that of diet (11) and also seems to be age dependent (12). In life sciences, sulfur isotopic ratios are mainly used to trace animals' diet in wildlife (13) and in stockbreeding (14) contexts. To this date, one study reports on bodily sulfur isotopic systematics, which shows no significant variations relative to diet in a murine model (15).…”
mentioning
confidence: 99%
“…Generally, in marine systems, studies have shown that both d 13 C values and d 15 N values of fish were higher than d 13 C and d 15 N of freshwater fish (France 1994;Doucett et al 1999;MacAvoy et al 2000;Garcia et al 2007). These patterns support the hypothesis that if pond smelt migrate between freshwater zone and coastal zone, pond smelt d 13 C values would change with growth.…”
Section: Isotopic Differences In Pond Smelt In Brackish Lagoonsmentioning
confidence: 98%